Evaluation of the effects of the Colombian blueberry (Vaccinium meridionale Swartz) on markers of high-density lipoprotein (HDL) function, inflammation and oxidative stress in women with metabolic syndrome (2019)
ABSTRACT: Introduction: Metabolic syndrome (MetS) is defined by the National Cholesterol Education Program- Adult Panel Treatment III (NCEP-ATPIII) as the presence of three or more cardiovascular risk factors (CVRF). Around one quarter of the world population have this syndrome that increases twice the risk of developing cardiovascular diseases (CVD) in the next 5 to 10 years, the leading cause of mortality in the world. The consumption of fruit and vegetables have been associated with lower risk of MetS. This benefit has been attributed to several bioactive components such as phytochemicals with antioxidant properties and modulation of cellular signaling pathways. Fruits of the gender Vaccinium are rich in phytochemicals with predominance of polyphenols, especially anthocyanins, which exhibit a high antioxidant capacity. Human intervention studies with Vaccinium have demonstrated beneficial effects on reducing traditional CVRF, inflammation and oxidative stress markers and to improve antioxidant capacity and HDL function. In Colombia grows the specie Vaccinium meridionale Swartz, also called agraz, with demonstrated high antioxidant capacity. However, fruit consumption in Colombia is insufficient, there is not agroindustrial development of Vaccinium crops in Colombia and the information about the effects of chronic consumption of agraz on inflammation, oxidative stress and antioxidant markers in people at high risk of CVD is very limited. General objective: To evaluate the effects of agraz (V. meridionale Swartz) on markers of high-density lipoprotein function, inflammation and oxidative stress in women with MetS. Methodology: Forty women (25–60 years) from Medellín-Colombia with MetS according to NCEP-ATPIII criteria were included in this double-blind and crossover study. Volunteers were assigned to consume daily a dose of 200 mL of reconstituted freeze dried agraz (equivalent to the total phenols present in 200 g of fresh agraz fruits) or placebo (without polyphenols) beverage over 4 weeks. After a 4-week washout period, they consumed the alternate treatment for additional 4 weeks. During the whole study, participants were asked to maintain their habitual physical activity and diet, except for the consumption of polyphenol-rich foods. Antropometrics [height, weight and waist circumference (WC)] and blood pressure were measured. Blood samples were obtained after a 12h overnight fasting to determine lipid profile and glucose at the beginning and end of each intervention period. In addition, the following markers were measured in samples obtained at the end of placebo and agraz periods: serum high-density lipoprotein (HDL) function markers (apolipoprotein-A1; paraoxonase 1 (PON1) activity; cholesterol efflux capacity), oxidative stress markers (serum myeloperoxidase -MPO) and advanced oxidation protein products -AOPP, and urinary F2-isoprostanes and 8-hydroxy 2 deoxyguanosine -8-OHDG), inflammatory markers (serum cytokines/chemokines and high sensitivity C-reactive protein (hs-CRP) levels, and the activation of nuclear factor-kB in peripheral blood mononuclear cells), endogenous antioxidant enzyme activity [superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx)], and serum total antioxidant capacity (TAC) determined by different methods [ABTS 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid); FRAP (ferric reducing ability of plasma) and ORAC (Oxygen Radical Absorbance Capacity)]. For the statistical analysis, after evaluating the data distribution, repeated measures ANOVA or Friedman test were used in the analysis of variables with baseline measures. Paired samples t-test or Wilcoxon test were used to evaluate the association between the end of each intervention period. In addition, we analyzed the women separated into two groups [obese and overweight, according to body mass index (BMI)] to evaluate the differential response of agraz consumption. Furthermore, the results were analyzed according to blood antioxidant response after agraz intake. Mann- Whitney U test or Student’s t-test were used to evaluate the associations between the independent groups. Finally, changes after agraz consumption (agraz minus placebo period) were calculated and the correlation between changes were determined with Pearson´s or Spearman´s correlation coefficient. All analyses were done using SPSS version 21 for Windows (SPSS, IBM Corporation, 2012). Differences with a value of p<0.05 were considered significant. Results. Forty women (47.2 ± 9.4 years old) with MetS finished the study with an adherence above 90%. No differences in macronutrient intake and physical activity were observed during the whole study. We already published the effects of agraz on anthropometric, blood pressure and blood lipid profile and glucose, in this population. In the whole group, there were not significant differences in HDL function, inflammation, oxidative stress and antioxidant markers, after comparing the end of both intervention periods (placebo versus agraz) (p > 0.05). Regarding HDL function, interestingly, only after agraz period there were significant positive correlations between PON1 activities and cholesterol efflux. Additionally, there were significant inverse correlations between changes in inflammatory markers and HDL function markers and positive correlations with oxidative markers. When analyzing the effects of agraz consumption on inflammation in women according to BMI classification, we found significantly reductions in hs-CRP levels in overweight women compared to obese women (p=0.028). Further, regarding oxidative stress effects, there was a significant reduction in urinary 8-OHdG levels in obese women after agraz consumption compared to placebo (p=0.031). Women who increased SOD activity after agraz consumption, compared to placebo, significantly reduced oxidative stress markers like 8-OHdG (p=0.022) and F2-isoprostane (p=0.034). Likewise, those women who increased GPx activity after agraz intake, significantly reductions in total cholesterol (p=0.023) and low-density lipoprotein cholesterol (LDL-c) (p= 0.022) levels. Finally, the increase in serum TAC (determined by ABTS) after 4 weeks of agraz consumption, was significantly associated with reduction in waist circumference. Conclusion: the chronic consumption of agraz over 4 weeks in a daily dose of 200mL (total phenols equivalent to 200g of fresh fruit) in 40 women with MetS did not significant improved HDL function, inflammation and antioxidant markers in the whole group. However, agraz consumption demonstrated to have a differential effect between obese and overweight women, with better anti-inflammatory effect in overweight women. Possibly, obese women have a more inflammatory state that requires a more drastic dietary intervention in this specific population. Interestingly, the effect on OxS markers was better in obese women. In addition, the group of women who increase these antioxidant parameters significantly improved CVRF such as reduction in lipid and DNA oxidation, total cholesterol, LDL-c and waist circumference. We demonstrated differential responses to agraz consumption in this population, which could suggest there is an individual variability influencing the beneficial effects of this fruit.